The Integration of AHP and Rank Order Centroid in a Decision Support System for Selecting Social Media for MSMEs - Putri, Mayang Anglingsari (Journal of Applied Informatics and Computing, 2026)
This study aims to develop a Decision Support System (DSS) to assist Micro, Small, and Medium Enterprises (MSMEs) in selecting the most optimal social media platform for promotional activities. In the digital era, choosing an appropriate platform is a critical factor in enhancing marketing effectiveness; however, many MSMEs face challenges in making informed decisions due to limited analytic capabilities and resources. To address this issue, the proposed system integrates the Analytic Hierarchy Process (AHP) to determine the relative importance of decision criteria and the Rank Order Centroid (ROC) method to assign weights to the alternatives. The evaluation criteria include audience reach, cost efficiency, and user engagement, which are considered essential factors in digital marketing strategies for MSMEs. The results indicate that Instagram achieved the highest score of 0.208 and is recommended as the most suitable social media platform for MSME promotion. TikTok ranked second with a score of 0.082, followed by Facebook with a score of 0.041. Furthermore, user validation testing demonstrates that the system is well accepted by MSME practitioners, as it provides recommendations that are accurate, structured, and easy to use.This research contributes by offering a technology-based decision-making solution that enhances the effectiveness of digital marketing strategies for MSMEs. The developed DSS serves as a practical and relevant tool to support promotional decision-making and to address the challenges of social media utilization in today’s competitive digital landscape.